Exploring the Intra Entrepreneurship-Employee Engagement-Creativity Linkage and the Diverse Effects of Gender and Marital Status - Kang, Tae-Won; Sinha, Paresha N.; Park, Chang-Il; Lee, Yong-Ki (Frontiers in Psychology, 2021)
This research hypothesized that the sub-dimensions of entrepreneurship (innovativeness, pro-activeness, risk-taking, and corporate social responsibility (CSR) support) affects employee engagement (organizational and job engagement), which leads to employee creativity. The findings demonstrate that innovativeness and CSR support affect creativity through mediating roles of organizational engagement and job engagement, whereas pro-activeness and risk-taking have no effect on organizational engagement and job engagement. And the finding shows that job engagement plays a mediating role in the relationship between organizational engagement and creativity. Also, the finding of ANN analysis shows that organizational engagement had the greatest importance on creativity in male-married and female-unmarried groups, while job engagement had the greatest importance on creativity in male-married and female-married groups. Among the sub-dimensions of entrepreneurship, CSR support was the most important in the female-unmarried, female-married, and male-unmarried group, respectively. On the other hand, innovativeness was the most important in the male-married group.